Diogo Simões Madeira, an example of Portuguese landowner in South-East Africa at the end of the 16th century - (:unkn) unknown (My University, 2022)
Diogo Simões Madeira is a prazero from South-East Africa who lived across the end of the 16th and the beginning of the 17th century. He constitutes a typical case study  to inform us  about the prazos system. The prazos was lands given by African landlords to powerful Portuguese. They used efficient armies of slaves to overthrow a leader, help him against a rival and then hold their land. Notwithstanding this military strength, the most stable prazeros were those with the best diplomatic skills and charisma, and the strongest were the ones ready to fully integrate African societies. At the beginning of the system, only a few  prazeros had a contractual relationship with the Crown, most of them occupied the region freely and did not want to pay any taxes to the Portuguese government. The situation evolved over time and by the middle of the 17th century, most prazeros had a contract with the Crown. To study the characteristics of the presence of Diogo Simões Madeira in South-East Africa, information was gathered from the two most renowned historians of the Portuguese presence in South-East Africa: Newitt, mainly  his work "Portuguese Settlement on the Zambesi", and Isaacman’s, "Mozambique, the Africanization of a European Institution". The most recent book of Eugenia Rodrigues, "Portugueses e Africanos nos Rios de Sena" was also carefully studied. Personal research in Lisbon archives allowed a deeper comprehension of the subject and valuable additions. Typical features of the prazero were thereby identified in Madeira’s personality. He used his army to acquire lands, secure them and their important earnings. The fact that the Portuguese administration did not succeed in controlling him is not  surprising either. However, this situation leads to an unseen plundering by a Portuguese administrator and Diogo Simões Madeira is considered for months as an enemy of the Crown permanently trying to escape the Crown authority. Therefore, the prazero Ma
Keywords: African Research